Photoelectron spectroscopy of terpenoids and prediction of their rate constants in atmospheric oxidation reactions - Wang, XiaoPeng; Tong, ShengRui; Ge, MaoFa; Wang, WeiGang; Wang, DianXun (Chinese science bulletin, 2010)
The electronic structures of six mono-terpenoids and two of their oxygenated derivatives were studied by He I photoelectron spectroscopy （PES）. The observed bands were interpreted on the basis of empirical arguments and theoretical calculations. The first vertical ionization potentials for ,8-pinene, ct-terpinene, terpinolene, y-terpinene, limonene, myrcene, citral, and ter- pinene-4-ol were determined to be 8.73, 7.57, 8.26, 8.30, 8.53, 8.68, 8.71, and 8.77 eV, respectively. Most of these values have not been determined by PES before. The correlations of the first vertical ionization potentials of these compounds to the natural logarithms of rate constants for their reactions with the radicals OH, NO3, and 03 were determined. The correlation coefficients for their reactions with OH, NO3, and O3 were 0.97, 0.91, and 0.95, respectively. This method is a powerful technique for pre- dicting the rate constants for the atmospheric oxidation reactions of terpenoids.